The effects of welding speed on microstructure and mechanical properties of dissimilar welded joints by CO2 Laser welding - Taskin, Mustafa (My University, 2014)
This study investigated the effects of welding speed on microstructure and mechanical properties of dissimilar welded joints (AISI 430 ferritic stainless steel and AISI 1010 low-carbon steel) by using CO2 laser beam welding. Laser beam welding (LBW) experiments were carried out under argon and helium shielding gas atmosphere at 2500 W constant heat input and 100-200-300 cm/min welding speeds. The microstructures of the welded joints were examined by optical microscopy, SEM, EDS, and X-ray analysis. The tensile strength of the welded joints was measured. The results of this study demonstrated that the best properties were observed at the specimens welded at a welding speed of 100 cm/min. © Carl Hanser Verlag.
Keywords: Carbon dioxide; Mechanical properties; Microstructure; Tensile strength; Welds; AISI 430 ferritic stainless steels; Heat input; Microstructure and mechanical properties; Shielding gas; Welding speed; Laser beam welding